Prototypes chez Proust : une recherche à corps perdu - Pierre Zoberman (Itinéraires)
Throughout the Recherche, Proust creates bodily prototypes as he assigns his characters identities that paradoxically de-individualize them. Specifically, while, on the one hand, the passing of Time shatters the illusion of the traditional aristoeracy’s permanence, the Jew and the homosexual, on the other hand, emerge as essences, decipherable and identifiable in and through their bodies, whose meaning thus becomes univocal and clear to the narrator and to which Proust’s also strives to give their proper names, i.e. those of the species to which their body assigns and consigns them.